Life-Threatening Laryngeal Edema and Hyponatremia during Hysteroscopy - Barbara Wegmüller; Kerstin Hug; Charlotte Meier Buenzli; Bernd Yuen; Marco Maggiorini; Alain Rudiger (Critical Care Research and Practice)
We report on a 43-year-old patient undergoing a hysteroscopic myomectomy. After 80 minutes of operation, the patient developed laryngeal edema, requiring emergency tracheostomy. Hyponatremia (serum sodium 78 mmoL/L) indicated an irrigation fluid absorption. The patient developed shock, acute respiratory distress syndrome, acute renal failure, and diffuse intravascular coagulopathy. Resuscitation including continuous venovenous hemodiafiltration was required. Finally, the patient made a full clinical recovery. Hysteroscopy usually has low risks. However, absorption of the irrigation fluid can result in life-threatening fluid overload and electrolyte disturbances. Accurate fluid balancing and limiting the operation time may prevent these complications.